Managing la mordida: gringo tourism, police shakedowns, and the nature of traffic ticket bribery in Quintana Roo, Mexico - Miller, Kirk (Deviant behavior, 2023)
This study examines collective knowledge about the practice of "la mordida," or police shakedowns, in the state of Quintana Roo, Mexico. The dual practices of police seeking payments and foreign tourists paying local police to resolve traffic stops is explored using data collected from web travel forums. Tourists to Quintana Roo share their experiences and developed wisdom for avoiding police stops, managing police shakedowns attempts during stops, the negotiation of la mordida after a stop has occurred, and the successful resolution of a stop, which may or may not include an exchange of money. The study describes the interactional strategies that compose elements of the la mordida frames present in tourist web forums, which illustrates the importance of the forums in both facilitating la mordida and contesting it among those visiting the area. The study contributes to literature focused on police corruption, deviant and coercive exchanges, crime victim scripts, and research focused on the resources that internet forums provide in avoiding, defending against, and facilitating coercive exchanges, especially in the context of tourism.